The Application of Lean Principles and DMAIC Approach to Improve Maintenance Performance in Jordanian Industry: Baraka Pack Jordan Company As a Case Study - Jalham, Issam S.; Al-Ashhab, Hiba (Jordan Journal of Business Administration, 2022)
Manufacturers are constantly trying to achieve the best productivity in order to preserve their position among their competitors and enhance the confidence of their customers. Once machines breakdown, the process of production is disrupted, which results in a great loss. To avoid such losses, DMAIC approach was applied to reduce the total time of breakdowns during manufacturing. This study was conducted in Baraka Pack Jordan in Al-Hassan Industrial Estate (HIE), where the required data for this study was collected. Then, the analysis of breakdowns was carried out in order to find out the root causes. Necessary maintenance actions were recommended and carried out. The results of this study show that the total breakdown hours for each machine during the study period (before and after DMAIC and lean principles’ implementation) were reduced between 71.0% and 79.1%, while the average breakdown time per month was reduced by about 59.4%.